2015
DOI: 10.1515/revneuro-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of the pathophysiology of adverse neurodevelopmental outcomes in iron deficiency

Abstract: AbstractIron deficiency (ID) is a major public health problem worldwide among children aged 0–12 months. Several factors seem to contribute to the iron-deficient state in infancy, including insufficient antenatal and neonatal iron supplementation, exclusive breastfeeding, and early umbilical cord clamping after birth. The most concerning complications of ID, except for anemia, are related to altered long-term neurodevelopment. Clinical studies have shown a negative impact of ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 112 publications
0
19
0
1
Order By: Relevance
“…More recently, Galler et al (2011) reported that early childhood malnutrition was linked to problems in executive functioning in later childhood and adolescence, as well as increased levels of aggression (Galler et al 2013). Furthermore, iron deficiency in children has been linked to adverse social-emotional behavioral outcomes (Lozoff et al 2007;Lozoff et al 2008;Corapci et al 2010;Chang et al 2011;Lozoff et al 2014;Bakoyiannis et al 2015). Conversely, nutritional supplements of omega-3 fatty acids reduced behavioral problems among children aged 8 to 16 years old (Raine et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Galler et al (2011) reported that early childhood malnutrition was linked to problems in executive functioning in later childhood and adolescence, as well as increased levels of aggression (Galler et al 2013). Furthermore, iron deficiency in children has been linked to adverse social-emotional behavioral outcomes (Lozoff et al 2007;Lozoff et al 2008;Corapci et al 2010;Chang et al 2011;Lozoff et al 2014;Bakoyiannis et al 2015). Conversely, nutritional supplements of omega-3 fatty acids reduced behavioral problems among children aged 8 to 16 years old (Raine et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Children with iron deficiency face the risk of anemia and neurological disorders [35]. Iron supplements are generally given orally, intravenously or intramuscularly, but these common administration routes are often problematic for children.…”
Section: Discussionmentioning
confidence: 99%
“…C-WT, WT mice on a control diet; dID-WT, WT mice on an iron-deficient diet [Color figure can be viewed at wileyonlinelibrary.com] ID is one of the most important nutritional deficits, affecting almost 2 billion people worldwide. Maternal ID during gestation has been associated with important offspring neurological impairment, including motor and social neurological dysfunction (Bakoyiannis et al, 2015;Farrelly et al, 2017). When acquired during development, ID impacts OL maturation, which causes long-lasting hypomyelination in adulthood even after an iron-sufficient diet has been reinstated (Badaracco et al, 2008;Ortiz et al, 2004).…”
Section: Behavioral Correlation With Didmentioning
confidence: 99%